PENGARUH EFIKASI DIRI, SOFT SKILL, PENGALAMAN ORGANISASI TERHADAP KESIAPAN KERJA DENGAN MOTIVASI KERJA SEBAGAI VARIABEL MODERASI - Rais Khairul Umam; Dwi Puji Astuti (STKIP Pesisir Selatan, 2026)
This study aims to analyze the effects of self-efficacy, soft skills, and organizational experience on work readiness, with work motivation as a moderating variable among Accounting Education students at Universitas Negeri Semarang, cohort 2022. This study is motivated by increasingly complex demands in the workplace, requiring students not only to possess academic competencies but also confidence in their abilities, non-technical skills, and relevant organizational experience. This study employed a quantitative approach using a survey method. The sampling technique used was proportional random sampling with 118 respondents. Data were collected through a four-point Likert-scale questionnaire and analyzed using validity and reliability tests, multiple linear regression analysis, and Moderated Regression Analysis (MRA) with the assistance of IBM SPSS Statistics 27. The results showed that self-efficacy and organizational experience had no significant effect on work readiness, while soft skills had a positive and significant effect on work readiness. Furthermore, work motivation was found to strengthen the effects of self-efficacy, soft skills, and organizational experience on work readiness. These findings indicate that work motivation plays an important role in optimizing students’ potential to prepare themselves for entering the workforce.